Nicotine Vapor Method to Induce Nicotine Dependence in Rodents. Issue 1 (13th February 2018) - Kallupi, Marsida; George, Olivier
Abstract: Nicotine, the main addictive component of tobacco, induces potentiation of brain stimulation reward, increases locomotor activity, and induces conditioned place preference. Nicotine cessation produces a withdrawal syndrome that can be relieved by nicotine replacement therapy. In the last decade, the market for electronic cigarettes has flourished, especially among adolescents. The nicotine vaporizer or electronic nicotine delivery system is a battery‐operated device that allows the user to simulate the experience of tobacco smoking without inhaling smoke. The device is designed to be an alternative to conventional cigarettes that emits vaporized nicotine inhaled by the user. This report describes a procedure to vaporize nicotine in the air to produce blood nicotine levels in rodents that are clinically relevant to those that are observed in humans and produce dependence. We also describe how to construct the apparatus to deliver nicotine vapor in a stable, reliable, and consistent manner, as well as how to analyze air for nicotine content. © 2017 by John Wiley & Sons, Inc.